The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1049/iet-nbt.2018.5041
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of AgNPs exposure on physiological and biochemical changes and antioxidative defence system in wheat ( Triticum aestivum L) under heat stress

Abstract: The present study was designed to check the role of silver nanoparticles (AgNPs) on physiological, biochemical parameters and antioxidants of wheat (Triticum aestivum L.) under heat stress. Plant extract of Moringa oleifera was used for AgNPs synthesis followed by characterization through UV-Vis spectroscopy, SEM, XRD and Zeta analyser. Heat stress was applied in range of 35-40°C for 3 hrs/ day for 3 days to wheat plants at trifoliate stage. Heat stress decreased the RWC (13.2%), MSI (16.3%), chl a (5.2%), chl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(16 citation statements)
references
References 66 publications
(89 reference statements)
1
15
0
Order By: Relevance
“…Antioxidant enzymes are located among different sites of plant cells and work together with ROS-generating pathways to maintain ROS homeostasis (Zhang et al, 2015; Nejat and Mantri, 2017; Iqbal et al, 2019). The transcription factor APETALA2/ethylene response factor (AP2/ERF) plays an important regulatory role in signal transduction of the plant responses to various stresses including low temperature (Sakuma et al, 2002), which confers cold tolerance by promoting polyamine turnover, antioxidant protection, and proline accumulation.…”
Section: Effects Of Cold Stress On Membrane Lipid Peroxidationmentioning
confidence: 99%
“…Antioxidant enzymes are located among different sites of plant cells and work together with ROS-generating pathways to maintain ROS homeostasis (Zhang et al, 2015; Nejat and Mantri, 2017; Iqbal et al, 2019). The transcription factor APETALA2/ethylene response factor (AP2/ERF) plays an important regulatory role in signal transduction of the plant responses to various stresses including low temperature (Sakuma et al, 2002), which confers cold tolerance by promoting polyamine turnover, antioxidant protection, and proline accumulation.…”
Section: Effects Of Cold Stress On Membrane Lipid Peroxidationmentioning
confidence: 99%
“…7 C ). Hussain et al [56] and Iqbal et al [57] reported that the total protein content was obstructed by the presence of AgNPs. In addition, Mehrian et al [58] revealed variations in amino acids content in tomato plants treated with AgNPs compared with untreated plants.…”
Section: Resultsmentioning
confidence: 99%
“…According to Mishra et al [59] plants produce different types of osmolytes such as proline as a counter‐part to abiotic stresses and involved in stress tolerance through osmotic adjustment and ROS detoxification. Mohamed et al [60] and Iqbal et al [57] reported overproduction of proline in wheat plants. Similarly, Mehmood and Murtaza [61] observed an increase in organic solutes due to AgNPs in pea ( Pisum sativum L.) seeds.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations